A systematic review of peer-assisted learning in fully online higher education distance learning programmes. (3rd July 2022) - Tibingana-Ahimbisibwe, Brenda; Willis, Sarah; Catherall, Sharon; Butler, Fran; Harrison, Roger
ABSTRACT: Peer-assisted learning (PAL) involves a student peer providing some form of support to a student mentee, usually participating at an earlier point in the same programme of study. PAL has been shown to have benefits for on-campus students. However, differences in on-campus and online programme delivery make it difficult to generalise these benefits to fully online distance learners (ODL). Of concern to providers of these types of programmes in higher education, are reports of increased student isolation, reduced motivation and early drop-out from their studies. Thus, providing PAL through an online environment may be one way to reduce these concerns. A systematic review of the published literature was performed to identify evidence of the potential benefits of formalised peer-assisted learning for students enrolled on a fully online, distance learning programme in higher education. A recognised methodology was used to search for relevant literature, and to synthesise results. Of the initial 2, 225 individual studies identified from the search, only four met the full inclusion criteria for this review. The results of the four studies were inconclusive; differences between types of academic programmes, the design of the peer-support and the way in which they had been examined and reported were found. As a result, there was little more than a suggestion that in higher education, formal online peer-support might benefit fully online distance learners in some way.